TỔNG HỢP ALUMINOSILICAT MAO QUẢN TRUNG BÌNH TỪ MẦM ZEOLIT X TRONG MÔI TRƯỜNG AXIT - Hảo, Phạm Mạnh; Đôn, Tạ Ngọc; Bái, Trịnh Xuân; Linh, Nguyễn Thị; Bình, Nguyễn Đình; Hà, Nguyễn Thu; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2012)
Mesoporous aluminosilicates assembled from zeolite X seeds with the molar compositions of 4Na2O.Al2O3.4SiO2.160H2O and having three-dimensional (3D) structures were synthesized successfully from metakaolin in the presence of nonionic octyl-phenyl polyethylene ether (Triton X -100) in acid media. The effect of stir time on the structure of materials was investigated. These materials were characterized by nitrogen adsorption isotherm, TEM, IR and TGA-DSC. The results indicated that the material synthesized with stir time of 20 hours has wormhole mesostructure with the narrow porous size distribution of 3.6 nm, BET surface area of 692 m2/g and porous volume of 0.79 cm3/g.